The Effectiveness of Grammarly Application on the Students' Argumentative Writing Progress - Resiana, Amellia Tasya; Zamzam, Ahmad; Putera, Lalu Jaswadi; Amrullah; Arfah, Hajriani (Program Studi Pendidikan Bahasa Inggris, 2024)
This research aims to describe the effectiveness of Grammarly feedback on students' progress in argumentative writing. Grammarly is an online automated writing evaluation tool that focuses on giving feedback on the language used in any type of writing. The tool was used in argumentative writing courses for 34 third-semester students at a state university in Mataram. The research used a descriptive qualitative method to collect data on the students' perceptions. The data was collected using validated questionnaires with a four-point Likert scale and supported by interviews. The findings show that students generally had positive perceptions of Grammarly. They found it effective for identifying and correcting errors in their writing, especially in grammar, punctuation, and sentence structure. They considered the correctness feature to be the most helpful. Additionally, they believed that using Grammarly improved their motivation and grammatical competence in argumentative writing. However, some participants had negative perceptions of Grammarly's weaknesses, particularly in providing feedback on the arrangement of thesis statements, counter-arguments, and the use of evidence in argumentative writing.